Party System Change in Eastern and Western Germany Between Convergence and Dissimilarity - Aiko Wagner (German Politics, 2022)
This paper compares the evolution of critical characteristics of the party systems in Eastern and Western Germany since unification. While the institutionalisation hypothesis implies that the party system in Eastern Germany should adjust towards its Western German counterpart, the ongoing dealignment suggests a loosening of party-voter-linkages and, ultimately, non-institutionalisation in Eastern Germany and party system de-institutionalisation in Western Germany. However, both hypotheses predict a convergence. Against the backdrop of persisting regional differences in party strengths, a third hypothesis assumes that Eastern and Western Germany still have two distinct party systems thirty years after reunification. Using election results and survey data since the 1990s, we inspect the development of five indicators of party systems – volatility, vote-switching, electoral availability, fragmentation, and differences in vote shares – in light of the hypotheses. There are three main results: First, most of the indicators point to party system institutionalisation in Eastern Germany and convergence to Western Germany in the 1990s. Second, for the last 20 years or so, the indicators point to parallel developments of dealignment and partial party system de-institutionalisation. Third, regarding the specific parties and their vote shares, there has been no convergence between Eastern and Western Germany.
Keywords: 300